Study of the impact of Industry 5.0 technologies on operational excellence: Insights into agility, innovation, and sustainability - Boumsisse, Imane; Benhadou, Mariam; Haddout, Abdellah (International Journal of Innovative Research and Scientific Studies, 2025)
Industry 5.0 marks an evolution from Industry 4.0 by integrating advanced technologies such as artificial intelligence, IoT, and big data while taking a more human-oriented and sustainability-oriented approach. This new industry framework is profoundly changing operational excellence practices, driving agility, resilience, continuous innovation, and increased collaboration with customers. This study focuses on assessing the impact of Industry 5.0 technologies on several dimensions of operational excellence, namely productivity, quality, agility, innovation, customer satisfaction, resilience, and sustainability. The aim is to examine how these innovations impact contemporary industrial practices. An empirical study on the adoption and perceived impact of Industry 5.0 technologies was conducted with professionals from various industry sectors. A statistical analysis of the data collected made it possible to determine the correlations between the adoption of these technologies and the operational performance observed. The results show that the integration of Industry 5.0 technologies significantly improves process efficiency, productivity, and organizational agility. However, the effects on innovation and customer satisfaction are still limited, suggesting that these areas are being less tapped. In addition, moderate progress has been made on sustainability and resilience, including through better energy management and increased flexibility in supply chains.